Educational development and expenditures on education in Mainpur - Marchang, Reimeingam (IASSI Quarterly: Contributions to Indian Social Science)
Educational level and consumption expenditure (CE) on education have grown concurrently and significantly in Manipur as in India. Manipur continues to spend a larger proportion of CE on education when compared to the country's level, particularly in rural areas. Urban people continue to spend more CE on education than their rural counterparts in it. Concurrently, literacy and educated rates were higher in the State than in the country. In Manipur, the public expenditure (PE) on education has considerably declined in recent times despite educational development. Per capita PE on education has substantially increased due to inflation and that attributes to a costlier educational service. Spending on education must be increased to enhance educational enrolment and attainment and to improve earnings and economic condition of individuals and the economy. - Reproduced
Keywords: Education, Development, Infrastructure, Expenditure, Manipur